Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Kesehatan di Bursa Efek Indonesia - Sustiyatik, Enni; Jauhari, Tontowi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2021)
Profitability is the company's ability to generate profits. There are several factors that affect the company's profitability, namely Liquidity, Leverage and Company Size. Based on this premise, this study aims to determine the effect of Liquidity, Leverage and Company Size on the Profitability of Healthcare Companies listed on the Indonesia Stock Exchange (IDX). This type of research is explanatory research which explains the causal relationship between the intermediate variables through hypothesis testing. The population of this study are all health companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. Sampling using purposive sampling technique in order to obtain 12 companies. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is multiple linear regression test using SPSS. From the results of this test, it can be concluded that liquidity has a significant positive effect on company profitability. Leverage has a significant negative effect on the profitability of health companies. Company size has a significant positive effect on the profitability of health companies. Liquidity, Leverage, Company Size jointly affect the profitability of Healthcare companies.